HUBUNGAN KONDISI LINGKUNGAN FISIK RUMAH DAN PERILAKU ANGGOTA KELUARGA DENGAN KEJADIAN PNEUMONIA PADA BALITA (Studi Kasus di Wilayah Kerja Puskesmas Magelang Selatan Kota Magelang) - Diah Kusumawati; Suhartono Suahartono; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pneumonia remains a global health problem. Pneumonia is an acute infection of the air passages that have the potential to cause significant respiratory difficulty because of inflammation proscess in which there is a consolidation caused cavities alveolar filling by exudate. The risk factors that affect the incidence of pneumonia include the physical environment condition of the house and the behavior of family members who are not healthy. The highest incidence of pneumonia in 2014 contained in South Magelang Health Center, amounting to 232 cases. This research aims to determine the relationship between the physical environment condition of the house and behavior of family members with pneumonia incidence on children under five years old in the working area of South Magelang Health Center, Magelang City. This research uses an observational analytic research with case control study design. Samples in the this research were 90 children aged 12-59 months consisting of 45 case groups and 45 control groups with age and sex of the children matching. Analysis of data using Chi Square test with a 95% confidence interval. The results showed that from risk factors of physical environmental of a house had significant relationship with pneumonia incidence on children such as the level of residential density (p = 0.018; OR = 3.143), the intensity of natural lighting in the home (p = 0.033; OR = 2.768), and home humidity levels (p = 0.017; OR = 3.231), while risk factors of family members behavior had significant relationship with pneumonia incidence on children such as the habit of opening the windows in the morning and during the day (p = 0.019; OR = 3.007). Conclusion of this research are the physical environment condition of the house and the behavior of family members had significant relationship with pneumonia incidence on children include the level of residential density, the intensity of natural lighting in the the house, the house humidity levels, and the habit of opening the windows in the morning and during the day.